2019
DOI: 10.1002/jbt.22369
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin protected against isoniazide‐induced HepG2 cell apoptosis by activating the SIRT1/ERK pathway

Abstract: Isoniazid (INH) is one of the most commonly used antituberculosis drugs, but its clinical applications have been limited by severe hepatic toxicity. Quercetin (Que), a natural flavonoid, has been proved to have many medicinal properties. This study aimed to clarify the possible protective effects of Que against INH‐induced hepatotoxicity using HepG2 cells. Our results indicated that Que significantly increased cell viability, superoxide dismutase, and GSH levels, while decreased alanine aminotransferase/aspart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…After SIRT1 silenced, the effect of curcumin was partially inhibited. This conclusion is consistent with many other studies, which had confirmed that isoniazid inhibited SIRT1 expression in HepG2 and HL7702 cells and downregulated SIRT1/PGC‐α/NRF1 pathway (Zhang, Li, et al, 2019; Zhang, Tang, et al, 2017; Zhang, Zhang, et al, 2019). Similarly, in 2018, Portale‐Perez DP's team found that, with SIRT1 inhibited, the activity of NAT2 increased; with SIRT1 stimulated, the result was quite opposite (Salazar‐Gonzalez et al, 2018; Turijan‐Espinoza et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…After SIRT1 silenced, the effect of curcumin was partially inhibited. This conclusion is consistent with many other studies, which had confirmed that isoniazid inhibited SIRT1 expression in HepG2 and HL7702 cells and downregulated SIRT1/PGC‐α/NRF1 pathway (Zhang, Li, et al, 2019; Zhang, Tang, et al, 2017; Zhang, Zhang, et al, 2019). Similarly, in 2018, Portale‐Perez DP's team found that, with SIRT1 inhibited, the activity of NAT2 increased; with SIRT1 stimulated, the result was quite opposite (Salazar‐Gonzalez et al, 2018; Turijan‐Espinoza et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Quercetin (3,3 ,4 ,5,7-pentahydroxyflavone) is a flavonoid that is widely found in several foods, including grains, fruits, vegetables, and tea [8]. Quercetin has anti-inflammatory, anti-oxidant, and anti-apoptosis properties and thus, it recommended as a nutritional supplement for animals [9][10][11][12]. Moreover, quercetin can prevent oxidative stress by scavenging free radicals, removing oxidation products, and stimulating antioxidant enzymes in many animal models [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…However, MGC803/DDP cells showed significant resistance to cisplatin. Bax, cleaved-caspase-3 and cleaved-PARP were regarded as factors of regulating cell apoptosis [24]. Our experimental results showed that the above protein levels were markedly upregulated by cisplatin in MGC-803 and MGC-803/ DDP cells.…”
Section: Discussionmentioning
confidence: 67%